Efficacy of seed soaking in different phytoextracts for the management of charcoal rot (Macrophomina phaseolina (tasi) Goid) of sesame: Efficacy of seed soaking in different phytoextracts for the management of charcoal rot (Macrophomina phaseolina (tasi) Goid) of sesame - K N GUPTA; AKSHAY SALBARDE; RAJNI BISEN (Journal of Oilseeds Research, 2023)
The effect of sixteen plant extracts were evaluated for the management of root & stem rot of sesame by seed soaking method under in-vivo (sick plot condition) at 20 percent of concentrations in two sesame varieties. In variety RT-346 garlic extract was found most effective as a seed treatment among all the tested plant extract against M. phaseolina by 78.44 percent of healthy plant followed by the onion 77.28 percent. In VRI-1 variety, garlic extract was found most effective as a seed treatment among all the tested plant extract against M. phaseolina by 79.66 per cent of healthy plant followed by the onion 75.81 per cent.